Evaluasi Kualitas Ruang Publik Kawasan Reklamasi di Pesisir Pantai Kawasan Perkotaan Raha - Adnan Affan Akbar Botanri; Ririn Eka Sakinah; Pieter Thomas Berhitu (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The reclaimed coastal area in the Raha Urban Area is a public space developed to support the waterfront city concept; however, its utilization has not been fully optimal. This study aims to evaluate the quality of public space and identify the characteristics of visitor behavior in the area. The research uses a descriptive method with a qualitative and quantitative approach (mixed methods). Data were collected through field observations, documentation, interviews, and questionnaires distributed to visitors as research respondents. Visitor behavior was analyzed using the Behavior Setting method by observing the types of activities, visiting times, and patterns of space use by visitors. Meanwhile, the quality of the public space was evaluated using the Public Space Index (PSI) method which assesses five main aspects: inclusiveness, meaningful activities, comfort, safety, and enjoyment. The results show that the public space is actively used, especially on weekends. However, several issues remain, such as waste management, unorganized street vendors, and limited supporting facilities. The PSI score of 72.04 indicates that the quality of the public space falls into the “fairly good” category, but still requires improvement, particularly in terms of comfort and safety.